(3QSGdI GdEfUfGAs - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj,J (B433 (3g` s
(3ChdgG (B:s
(3ef gGOi GdeSJLjfjf GdefJbe ef GdeTQcjf HSja ehdGfG Edg GdYGdejf hCfJe eYGTQ GdehMOjf HGdEfUGA cKjQ Gdehdi YOOce hRcG CYeGdce s
(3BNQgG (B:s
(3acCfi Hce hLjhT GdaQL bO fRdJ hCYdGeg bO fTQJ hgh MSHi hKbJi hHg GSJYjf JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3HgG fXGe GdJYbjHIs
(3QSGdI ef QSGFd GdOQhRs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3fSNI KGdKI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B79s
Keywords: (3GdJhMjO hGdedd hGdfMds